2017
DOI: 10.3389/fphar.2017.00464
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of TNF-α-Induced Inflammatory Injury in Endothelial Cells by Ginsenoside Rb1 via Inhibiting NF-κB, JNK and p38 Signaling Pathways

Abstract: It is currently believed that inflammation plays a central role in the pathophysiology of atherosclerosis. Oxidative stress and redox-sensitive transcription factors are implicated in the process. Ginsenoside Rb1, a major active ingredient in processed Radix notoginseng, has attracted widespread attention because of its potential to improve cardiovascular function. However, the effects of ginsenoside Rb1 on tumor necrosis factor-α (TNF-α)-induced vascular endothelial cell injury and the underlying molecular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 44 publications
9
73
0
Order By: Relevance
“…We further demonstrate that Panx1 expression by cultured human vascular smooth muscle cells (SMC) is unaltered by TNF treatment ( Supplemental Figure 1D ). Previous studies have found TNF to reduce cell viability (Zhou et al, 2017). However, 24 hr TNF treatments ranging from 2.5-100 ng/mL for 24 hr did not alter HUVEC viability as measured by intracellular ATP levels, caspase-3 cleavage, or by cell morphology ( Supplemental Figure 1E-G ).…”
Section: Resultsmentioning
confidence: 98%
“…We further demonstrate that Panx1 expression by cultured human vascular smooth muscle cells (SMC) is unaltered by TNF treatment ( Supplemental Figure 1D ). Previous studies have found TNF to reduce cell viability (Zhou et al, 2017). However, 24 hr TNF treatments ranging from 2.5-100 ng/mL for 24 hr did not alter HUVEC viability as measured by intracellular ATP levels, caspase-3 cleavage, or by cell morphology ( Supplemental Figure 1E-G ).…”
Section: Resultsmentioning
confidence: 98%
“…Ginsenoside Rf showed an inhibitory effect on the inflammatory mediators downstream of p38/NF-κB activation, such as the reduction of IL-1β, IL-6, TNF-α, NO, and ROS productions, on TNF-α-stimulated HT-29 intestinal epithelial cells and RAW264.7 mouse macrophage cells [18]. Moreover, its anti-inflammatory activity, along with ginsenoside Rb1 and Rg1, was reported, and anti-oxidation and the inhibition of NO synthesis were proposed as its mechanism [19,20].…”
Section: Ginsenosides In Anti-inflammationmentioning
confidence: 94%
“…Ginseng is a herb that has been used since years ago in Asian countries as it possesses various therapeutic benefits which come from its active compound called ginsenoside (Kim, Yi, Kim, & Cho, 2017;Nuri, Yee, Gupta, Khan, & Ming, 2016). Ginseng has appealing biological properties including the effects on CVDs such as anti-inflammatory, anti-oxidative, and protective toward human cell (Zhou et al, 2017). These abilities arose the chosen of ginseng to be applied in cardiovascular applications.…”
Section: Discussionmentioning
confidence: 99%